First record of albino Aesculapian Snake (Elaphe longissima) in Slovenia - Miha Krofel (Natura Sloveniae)
The article presents the discovery of an albino Aesculapian Snake (Elaphe longissima) at Sredma near Brestrnica (UTM WM46, NE Slovenia). The specimen (gender unknown) was about 120 cm long adult with red eyes, pale yellowish underside and dark yellow head, dorsal side and flanks. This is most likely the very first find of this kind in Slovenia.